What can be learned from practical cases of green economy? –studies from five European countries. (15th December 2016) - Pitkänen, K.; Antikainen, R.; Droste, N.; Loiseau, E.; Saikku, L.; Aissani, L.; Hansjürgens, B.; Kuikman, P.J.; Leskinen, P.; Thomsen, M.
Abstract: The transition to green economies has been mediated by concrete cases and experiments in a variety of different industrial and social sectors. What is lacking, is research that would synthesize key findings and "lessons learned" across a variety of cases. In this study, we explore ten cases of green economy of different sectors and approaches from five European countries and identify factors that have had critical importance for the success or failure of the cases. Our paper reveals similarities across small and large scale cases and different approaches for implementing green economy. We identified critical factors related to economic viability, public funding, technological development, impact assessments, public policies and regulation, social capital, leadership and coordination as well as public acceptability and image. According to our results, transition to green economies requires negotiation between potential trade-offs among multiple goals, and interests of various stakeholders. The mutual benefits can be communicated through valid impact assessments and the integration of R&D into the practical implementation. Securing the continuity of funding and leadership is crucial in successful experiments and attention should be paid to fostering social capital among stakeholders. Instead of any single critical factor, the practical implementation of green economy is related to a multiplicity of factors and causalities depending on the context. The challenges with the practical implementation of green economy can only be met with patient, careful and far-sighted planning of green economy initiatives as well as continuous learning from past experiences. Highlights: The paper explores 10 cases of green economy applying multiple scientific approaches. Transition to green economy requires negotiation and balancing between multiple goals. Securing the continuity of funding and leadership is crucial. Integration of R&D into the practical implementation has many positive effects. Building on existing networks can be helpful in committing stakeholders.